Irrigação plena e com déficit em diferentes estádios fenológicos da cultura do girassol no semiárido cearense - Silva, Alexandre Reuber Almeida da (2012)
Crops have phenological stages with less susceptibility to water deficit, in which the strategy of deficit irrigation management can be employed in order to maximize production per unit of irrigation water. Thus, the purpose of this research was to evaluate the responses of sunflower cultivation with full irrigation and with different water deficits durin g its phenological stages in order to collect information on the technical feasibility of the irrigation deficit in the sunflower crop, for the conditions of the semiarid in state of Ceara, Brazil. In the field the experiment was conducted at Experimental Farm Vale do Curu, in Pentecoste (Ceara, Brazil) under experimental design of randomized blocks with four replications and eight treatments, defined in function of the time of water deficit induction in the three sunflower phenological stages (vegetative, flowering and production formation), corresponding to the occurrence of water deficit in one, two or three stages. The water deficit irrigation level employed consisted of half the irrigation evaluated as being full irrigation. All the cultural and phytosanitary practices required was carried. In order to measure the effects of the treatments it was evaluated, at the end of each developmental stage, the following variables: leaf temperature, photosynthesis rates, transpiration, stomatal conductance, internal concentration of CO2, instantaneous efficiencies and intrinsic water use, plant height, quantity of leaf, stemdiameter, leaf area, dry biomass production of the constituents of the aerial part (stem, leaf, petiole and chapter) and the participation of each element in relation to the production of total dry matter (partition). On the occasion of harvest time, it was evaluated the components of production (diameter of chapter, mass of 1000 achenes and oil and protein content), the income potential of producing acheness, oil and protein, and the indices of efficiency of water use to produce achenes, oil and protein. The variables were subjected to statistical analysis, performing analysis of variance (F test) and Tukey's test to compare means. It was also determined the coefficients of sensitivity to water deficit (KY) isolated in stadiums and in the cycle of the crop through the relationship between relative income decrease and relative evapotranspiration deficit. The results presented that the temperature and leaf gas exchanges howed no effects of the applied water stresses, regardless of the time when these were applied. The times of evaluation influenced all variables related to gas exchange, except for the intrinsic efficiency of water use. The plant height, leaf number and stem diameter were negatively affected by the isolated effects of irrigation deficits and evaluation times. The irrigation deficit and the evaluation time interacted and affected leaf area, dry mass of leaf, petiole, stem, capitulum and total dry mass. The d eficit irrigation did not change the partition of dry matter. Changes were observed in capitulum diameter, in the mass of one thousand achenes, in the achene oil content, in the achene, oil and protein production potentials, and in the water use efficiency in the production of achenes and oil (for the applied water deficits). The management strategy of water deficit during the vegetative and flowering stages contributed to the achievement of an achene production potential at a level equivalent to that achieved in cultivation with full irrigation throughout the growing season. Regardless of the phenological phase, the water deficit exerted a positive effect on the efficiency of water use in the achene production. The incidence of water deficit during the flowering stage was more advantageous to the efficiency of water use in oil production than at any other stage, and did not influence the efficiency of water use in protein production, regardless of phenological stage on which it happened. Sensitivity to water deficit quantified by the coefficient of sensitivity to water stress (K Y) varied in the following decreasing order: production formation, vegetative and flowering, with water deficit occurring in only one developmental stage. For the deficit conditions in two stages, the coefficient KY showed that the lack of water has the greatest impact on sunflower achene yield when it occurs in both vegetative and production formation stages. As the K Y values were less than 1 at all stages, it is concluded that the sun flower culture showed a low sensitivity to the water deficits applied, showing, therefore, vulnerability to water deficit irrigation practice throughout its cycle.